2022
DOI: 10.1088/1748-9326/ac8daa
|View full text |Cite
|
Sign up to set email alerts
|

Post-Soviet changes in cropping practices in the irrigated drylands of the Aral Sea basin

Abstract: Water withdrawals for irrigated crop production constitute the largest source of freshwater consumption on Earth. Monitoring the dynamics of irrigated crop cultivation is crucial for tracking crop water consumption, particularly in water-scarce areas. We analyzed changes in water-dependent crop cultivation for 650 000 km2 of Central Asian drylands, including the entire basin of the Amu Darya river, once the largest tributary to the Aral Sea before large-scale irrigation projects grossly reduced the amount of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…However, climatic changes have spurred new shifts that challenge both currently irrigated and traditionally dryland systems' capacity to cope with growing scarcity of water supplies. This is evident in practices such as the increased emphasis on wet season cropping in the Aral Sea basin (Rufin et al 2022), or the redesign of viable cropping strategies prompted by irrigation retirement in the Great Plains region of the US (Núñez et al 2022). In areas where agriculture depends heavily on irrigation, looming cutbacks in water availability underscore the need to understand how the transition from irrigated to non-irrigated systems will play out, along with its economic and environmental implications.…”
Section: Irrigated and Dryland Agricultural System Transitionsmentioning
confidence: 99%
“…However, climatic changes have spurred new shifts that challenge both currently irrigated and traditionally dryland systems' capacity to cope with growing scarcity of water supplies. This is evident in practices such as the increased emphasis on wet season cropping in the Aral Sea basin (Rufin et al 2022), or the redesign of viable cropping strategies prompted by irrigation retirement in the Great Plains region of the US (Núñez et al 2022). In areas where agriculture depends heavily on irrigation, looming cutbacks in water availability underscore the need to understand how the transition from irrigated to non-irrigated systems will play out, along with its economic and environmental implications.…”
Section: Irrigated and Dryland Agricultural System Transitionsmentioning
confidence: 99%
“…As the largest inland terminal lake in arid Central Asia, the Aral Sea plays a key role in the ecological environment and water resource utilisation. However, along with population growth, the rapid expansion of croplands in the middle and upper reaches of the Amu Darya River and Syr Darya River (Rufin et al, 2022), which represent the main water sources of the Aral Sea, has significantly decreased the incoming water to the lake basin. In addition, over the past 100 years, glacial recession and an increase in evapotranspiration caused by global warming have exacerbated the severity of this problem in Central Asia (Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, research conducted by Huang et al (2022) and Zhang et al (2022), who analysed glacier changes over the past century, showed that the inland lakes in Central Asia decreased, while the higher-altitude alpine lakes increased significantly along with glacier meltwater, stressing the importance of human activities in the lake area reduction of the Aral Sea. Rufin et al (2022) reported that croplands increased from 4.400×10 4 km 2 in 1987 to 5.200×10 4 km 2 in 2017, with more than a 200% increase in double-cropping irrigation lands, followed by a rapid urban expansion and sharp rise in water consumption in the last 20 years (Yan and Li, 2023), contributing to the problem. A comparative analysis of climatic and anthropogenic factors by Yang et al (2020a) concluded that anthropogenic factors were the main cause of the reduction in the lake area.…”
Section: Introductionmentioning
confidence: 99%